Super-hydrophobic catalyst for catalyzing aqueous phase coupling of ethanol as well as preparation method and application of super-hydrophobic catalyst
By ball milling the nickel-based catalyst with the hydrophobic polymer PDVB, the problems of C-C bond fracture and water molecule poisoning in the Guerbet coupling reaction are solved, and the ethanol conversion rate and high carbon alcohol selectivity are improved, achieving More efficient catalytic effects.
Patent Information
- Application Number
- CN202411410563.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Ni-based monometallic catalysts tend to cause C-C bond breakage in the process of promoting alcohol dehydrogenation and hydrogenation, increasing by-product generation, and the catalyst has insufficient hydrophobic properties due to the formation of water molecules, resulting in 'poisoning' problem, which limits its coupling in Guerbet Application in reaction.
By ball milling the nickel-based catalyst with the hydrophobic polymer PDVB, a superhydrophobic catalyst is formed, which improves the hydrophobic properties of the catalyst, reduces the occurrence of side reactions, and enhances the catalytic activity and selectivity of high-carbon alcohols.
The ethanol conversion rate and selectivity of C6+ alcohol products in the ethanol coupling reaction are significantly improved, the catalyst deactivation phenomenon is reduced, and the catalyst reaction activity and economic benefits are improved.
Smart Images

Figure CN119281328A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a super hydrophobic catalyst, specifically, a plurality of Ni-based catalysts coupled with a hydrophobic polymer PDVB. The present invention also relates to the application of the super hydrophobic catalyst and a method for catalyzing the synthesis of higher carbon alcohols by catalyzing ethanol in water phase Technical Background
[0002] In the context of coping with increasingly severe environmental problems, especially the tight energy supply caused by excessive consumption of fossil resources, the exploration and application of renewable energy has become a global focus, accelerating the transformation of the energy structure. As a unique renewable carbon resource, biomass plays an important role in sustainable energy substitution and carbon emission reduction. Given the maturity of industrial fermentation technology, ethanol converted from biomass sugars has been successfully commercialized, becoming a leader in the field of biofuels and occupying a dominant position in the market.
[0003] The blending of ethanol in gasoline not only reduces the dependence on pure fossil fuels, but also optimizes the combustion process by providing additional oxygen, improves engine efficiency, and effectively reduces pollutant emissions. However, some inherent properties of ethanol, such as low cetane number, low energy density and high auto-ignition temperature, limit its widespread application in diesel engines. In contrast, high-carbon alcohols (such as isoheptanol) are considered to be more ideal candidates for diesel additives due to their higher cetane number, energy density and lower auto-ignition temperature, as well as good compatibility with traditional fuel systems.
[0004] For many years, researchers have been committed to developing efficient heterogeneous catalysts to optimize the Guerbet coupling reaction. Initially, some progress was made using catalysts with acid-base bifunctionality (such as MgO, MgAlO, etc.), but the high reaction temperature and the resulting side reactions limited their application. Subsequently, the introduction of transition metals (such as Ni, Cu, etc.) as promoters, combined with homogeneous bases, significantly increased the reaction rate. In particular, Ni-based catalysts have received widespread attention in the field of ethanol coupling due to their low cost and excellent catalytic activity.
[0005] Compared with expensive precious metal catalysts, Ni-based non-precious metal catalysts not only reduce costs but also improve economic benefits. However, while Ni-based monometallic catalysts promote alcohol dehydrogenation and hydrogenation, they are also prone to CC bond breakage and increase the formation of by-products. To this end, researchers are exploring ways to optimize the performance of Ni-based catalysts and improve their selectivity and stability by constructing bimetallic or multimetallic catalysts, regulating catalyst structure, and adding additives.
[0006] In the Guerbet coupling transformation of low-order alcohols to high-order alcohols, a series of complex cascade reactions are the core, including alcohol dehydrogenation, aldol condensation and dehydration, and hydrogenation saturation of the final product. In this process, the key to promoting aldol condensation is to select a suitable catalyst, and at the same time, it is necessary to solve the problem of catalyst "poisoning" caused by the generation of water molecules, which puts higher requirements on the hydrophobic properties of the catalyst. Summary of the invention
[0007] In order to overcome the deficiencies of the above-mentioned prior art, the first object of the present invention is to propose a new super-hydrophobic catalyst formed by coupling a Ni-based catalyst with a hydrophobic polymer PDVB. This series of catalysts improves the hydrophobic properties of the simple nickel-based catalyst by simple ball milling with hydrophobic polydivinylbenzene, promotes the further coupling of low-carbon alcohols to higher alcohols, and the super-hydrophobic catalyst obtained after ball milling has improved the ethanol conversion rate and the selectivity of C6+ alcohol products for the synthesis of higher-carbon alcohols by ethanol coupling.
[0008] The second object of the present invention is to provide a method for synthesizing higher carbon alcohols from ethanol in aqueous phase catalyzed by a nickel-based-PDVB catalyst. The catalyst catalyzes the further coupling of low-carbon alcohols to higher alcohols. The ball-milled catalyst improves the ethanol conversion rate and the selectivity of C6+ alcohol products in the synthesis of higher carbon alcohols by ethanol coupling.
[0009] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:
[0010] To this end, the first technical solution provided by the present invention is as follows:
[0011] A super hydrophobic catalyst for catalyzing ethanol-water phase coupling is obtained by adding a nickel-based catalyst and a super hydrophobic polymer polydivinylbenzene into a ball mill at a mass ratio of 1:0-4, and ball milling for 2-10 hours at a rotation speed of 200-600 rpm.
[0012] Compared with rare precious metals such as Pd and Ru, transition metal Ni is abundant and has good catalytic performance in many typical reactions. Therefore, Ni-based non-precious metal catalysts can well replace precious metal catalysts, reduce catalyst costs and improve economic benefits. At the same time, Ni-based metal catalysts have excellent catalytic activity for alcohol dehydrogenation and hydrogenation reactions.
[0013] Furthermore, in the above-mentioned super hydrophobic catalyst for catalyzing ethanol-water coupling, the mass ratio of the nickel-based catalyst to the super hydrophobic polymer polydivinylbenzene is 1:1.
[0014] Furthermore, the above-mentioned super hydrophobic catalyst for catalyzing ethanol-water coupling, the nickel-based catalyst is prepared by the following method:
[0015] S1, dissolving the nickel salt and the carbon source precursor in a solvent, stirring at room temperature to form a complex to obtain a homogeneous solution, and then heating and stirring to form a nickel-based catalyst gel precursor;
[0016] The molar ratio of the nickel salt to the carbon source is 1:2;
[0017] S2. The nickel-based catalyst gel precursor of S1 is placed in an inert gas atmosphere and subjected to a controlled high-temperature self-reduction carbonization reaction at 550° C. for 2 hours to obtain a nickel-coated carbon Ni@CA catalyst.
[0018] Furthermore, the above-mentioned super hydrophobic catalyst for catalyzing ethanol-water coupling, the nickel-based catalyst is prepared by the following method:
[0019] S1, dissolving nickel salt, tin salt and carbon source precursor in a solvent, stirring at room temperature to form a complex to obtain a homogeneous solution, and then heating and stirring to form a nickel-tin bimetallic catalyst gel precursor;
[0020] The molar ratio of Ni / Sn in the nickel salt and the tin salt is 20:1, and the molar ratio of Ni in the nickel salt to the carbon source precursor is 1:2;
[0021] S2. The nickel-tin bimetallic catalyst gel precursor of S1 is placed in an inert gas atmosphere and subjected to a controlled high-temperature self-reduction carbonization reaction at 550° C. for 2 hours to obtain a nickel-tin carbon-coated NiSn@CA bimetallic catalyst.
[0022] Although Ni-based metal catalysts have excellent catalytic activity for alcohol dehydrogenation and hydrogenation reactions, the selectivity of by-products is too high due to the strong CC bond breaking ability of Ni-based monometallic catalysts. Regarding the catalytic effect of the introduction of metal Sn, relevant studies have shown that in the aqueous phase reforming of oxygenated hydrocarbons, the introduction of Sn into Ni catalysts can significantly weaken the bond breaking activity of metal Ni on CO bonds, thereby inhibiting the methane obtained by hydrogenolysis in the reaction and promoting the formation of dehydrogenation products. We also found a similar promoting effect of the introduction of metal Sn on the formation of higher alcohols. The inhibitory effect of metal Sn on Ni CO bond breaking may inhibit the continued breaking process of the CO bond of the aldehyde intermediates formed by dehydrogenation. The released aldehyde intermediates further promote the subsequent aldol condensation process and achieve the growth of the carbon chain; this inhibitory effect of metal Sn on Ni CO bond breaking may be related to the Sn atoms located at the Ni defect site and the formation of surface Ni3Sn alloy.
[0023] Furthermore, the above-mentioned super hydrophobic catalyst for catalyzing ethanol-water coupling, the nickel-based catalyst is prepared by the following method:
[0024] S1. Dissolve nickel salt, carbon source precursor and L-cysteine in deionized water and stir until completely dissolved; evaporate the mixture at 80°C to gradually gel, and then dry at 100°C until completely dry;
[0025] S2, placing the nickel-based catalyst gel precursor of S1 in an inert gas atmosphere at 550° C. for a controlled high-temperature self-reduction carbonization reaction for 2 hours to obtain a nickel-coated carbon-sulfur Ni@CS catalyst;
[0026] The molar ratio of Ni in the nickel salt to the molar ratio of S in L-cysteine is 30:1; the molar ratio of Ni in the nickel salt to the carbon source precursor is 1:2.
[0027] Furthermore, in the above-mentioned super hydrophobic catalyst for catalyzing the coupling of ethanol with water, the nickel salt includes nickel nitrate, nickel chloride, nickel acetate, and nickel hydroxide, preferably nickel nitrate; the tin salt includes tin nitrate, tin citrate, and tin chloride, preferably tin chloride; and the carbon source is citric acid.
[0028] Furthermore, the above-mentioned super hydrophobic catalyst for catalyzing ethanol-water coupling, the polydivinylbenzene is prepared by the following method: 10g of purified divinylbenzene is stirred in 50g of solvent N,N-dimethylformamide at room temperature for 1h, then transferred to an autoclave, heat treated at 100°C for 12h, the obtained solid is washed with methanol, and dried at 100°C overnight to obtain polydivinylbenzene.
[0029] The second technical solution of the present invention is that the super hydrophobic catalyst is used to catalyze the coupling synthesis of higher alcohols in ethanol water phase.
[0030] The third technical scheme of the present invention is a method for synthesizing higher carbon alcohols from ethanol in aqueous phase using a super-hydrophobic nickel-based catalyst, wherein the super-hydrophobic catalyst described in the first technical scheme is used in a reaction system with a base, ethanol, and water, and the initial pressure is set to 0.1 MPa under a H2 atmosphere, and the reaction is carried out at 230°C for 12 hours to synthesize higher carbon alcohols;
[0031] Furthermore, in the method for synthesizing higher carbon alcohols from ethanol in aqueous phase using the superhydrophobic nickel-based catalyst, the mass ratio of superhydrophobic catalyst: base: ethanol: water is 0.3:0.88:5:5; the base can be sodium hydroxide or potassium hydroxide.
[0032] The reaction of synthesizing high-carbon alcohols from ethanol in water phase follows the Guerbet reaction principle, and the steps of the reaction can generally be divided into: (1) ethanol undergoes a catalytic dehydrogenation reaction at a metal active center; (2) the aldehyde intermediates formed by dehydrogenation undergo aldol condensation under the action of a base / acid; (3) after the high-carbon chain is formed by aldol condensation, the high-carbon chain is catalyzed by hydrogenation at the metal active center to form the desired high-carbon chain alcohol product.
[0033] Compared with the prior art, the present invention has the following advantages:
[0034] The technical solution provided by the present invention synthesizes the prepared nickel-based catalyst and the hydrophobic polymer PDVB by ball milling to form a super-hydrophobic nickel-based catalyst; The hydrophobic degree of the catalyst is greatly increased by ball milling the hydrophobic polymer, reducing the blockage of the internal pores of the catalyst due to the dehydration of the aldol condensation reaction and the water molecules in the reaction raw materials during the reaction, forming a "water poisoning" situation and causing the phenomenon of deactivation. The technical solution provided by the present invention applies the various super-hydrophobic catalysts prepared in the reaction of catalyzing the one-step synthesis of higher alcohols by aqueous ethanol, showing excellent catalytic efficiency, higher reaction activity, higher ethanol conversion rate and selectivity for C6+ higher alcohols are also increased. The technical solution provided by the present invention has simple catalyst preparation and low cost, and improves the reaction performance of the catalyst by simple ball milling, which is more conducive to its production application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Contact angles of nickel-based NiSn@CA catalyst and superhydrophobic polymer PDVB.
[0036] Figure 2 Oil phase gas chromatograms of nickel-based NiSn@CA catalyst and superhydrophobic nickel-based catalyst NiSn@CA-PDVB.
[0037] Specific embodiment
[0038] The following is a further description of specific embodiments of the present invention. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0039] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental raw materials used in the following examples can be purchased through conventional commercial channels unless otherwise specified.
[0040] Example 1
[0041] This example provides a method for synthesizing a hydrophobic polymer polydivinylbenzene PDVB, which is prepared by the following steps in sequence:
[0042] Divinylbenzene (DVB) monomer needs to be purified before use to improve the conversion rate. The steps are as follows: ① Weigh DVB into a separatory funnel, add NaOH solution to shake and wash, shake well and let stand to separate, take the upper layer of liquid, and repeat the operation three times; ② Wash the collected liquid with deionized water several times until it is neutral, use an appropriate amount of anhydrous Mg2SO4 to dry and remove water until the liquid is transparent; ③ Distill the liquid under reduced pressure, collect the effluent, and refrigerate for later use.
[0043] 10 g of purified divinylbenzene was stirred in 50 g of solvent N,N-dimethylformamide (DMF) at room temperature for 1 h, then transferred to an autoclave and heat-treated at 100°C for 12 h. The obtained solid was washed with methanol and dried at 100°C overnight to obtain polydivinylbenzene.
[0044] Example 2
[0045] This example provides a method for synthesizing superhydrophobic Ni@CA-PDVB.
[0046] The nickel-based catalyst Ni@CA and the hydrophobic polymer PDVB prepared in Example 1 were ball-milled at a rotation speed of 300 rpm for 4 hours in a super-hydrophobic mass ratio of 1:1 to obtain a super-hydrophobic nickel-based Ni@CA-PDVB catalyst.
[0047] The nickel-based catalyst Ni@CA is prepared by the following method:
[0048] S1, dissolving 3.68g of nickel nitrate and 5.6g of citric acid carbon source in 10g of deionized water, stirring at room temperature for 4h to form a complex to obtain a homogeneous solution, and then heating to 100°C and stirring to form a nickel-based catalyst gel precursor;
[0049] S2. The nickel-based catalyst gel precursor of S1 is placed in an inert gas atmosphere and subjected to a controlled high-temperature self-reduction carbonization reaction at 550° C. for 2 hours to obtain a nickel-coated carbon Ni@CA catalyst.
[0050] Example 3
[0051] The nickel-based Ni@CA catalyst prepared in Example 2 was applied to the reaction system of ethanol aqueous phase synthesis of higher alcohols. The reaction conditions were: 0.15 g of the prepared nickel-based catalyst, 0.88 g of sodium hydroxide, 5 g of ethanol, 5 g of water, an initial pressure of 0.1 MPa, and a reaction temperature of 230°C for 12 h. After the reaction, the reactor was cooled to room temperature, and then the gaseous products and liquid products were collected. The liquid products were centrifuged to obtain an oil phase, an aqueous phase, and a catalyst solid phase. The oil phase and the aqueous phase were then detected and analyzed by gas chromatography. The catalytic activity results of the products are shown in Table 1 below.
[0052] Example 4
[0053] The superhydrophobic nickel-based Ni@CA-PDVB catalyst prepared in Example 2 was applied to the reaction system of ethanol aqueous phase synthesis of higher alcohols. The reaction conditions were: 0.3 g of the catalyst prepared in Example 2, 0.88 g of sodium hydroxide, 5 g of ethanol, 5 g of water, an initial pressure of 0.1 MPa, and a reaction temperature of 230°C for 12 h. After the reaction, the reactor was cooled to room temperature, and then the gas phase product and the liquid phase product were collected. The liquid phase product was centrifuged to obtain an oil phase, an aqueous phase and a catalyst solid phase. The oil phase and the aqueous phase were then detected and analyzed by gas chromatography. The catalytic activity results of the products are shown in Table 1 below.
[0054] Example 5
[0055] This example provides a method for synthesizing superhydrophobic NiSn@CA-PDVB.
[0056] The prepared nickel-based catalyst NiSn@CA and the hydrophobic polymer PDVB prepared in Example 1 were ball-milled at a rotation speed of 300 rpm for 4 hours in a super-hydrophobic mass ratio of 1:1 to obtain a super-hydrophobic nickel-based NiSn@CA-PDVB catalyst.
[0057] The NiSn@CA is prepared by the following method:
[0058] S1, 3.68g nickel nitrate, 0.22g tin tetrachloride and 5.6g citric acid carbon source were dissolved in 10g deionized water, stirred at room temperature for 4h to form a complex to obtain a homogeneous solution, and then heated to 100°C and stirred to form a nickel-tin bimetallic catalyst gel precursor;
[0059] S2. The nickel-tin bimetallic catalyst gel precursor of S1 is placed in an inert gas atmosphere and subjected to a controlled high-temperature self-reduction carbonization reaction at 550° C. for 2 hours to obtain a nickel-tin carbon-coated NiSn@CA bimetallic catalyst.
[0060] Example 6
[0061] The nickel-based NiSn@CA catalyst prepared in Example 5 was applied to the reaction system of ethanol aqueous phase synthesis of higher alcohols. The reaction conditions were: 0.15 g of the prepared nickel-based catalyst, 0.88 g of sodium hydroxide, 5 g of ethanol, 5 g of water, an initial pressure of 0.1 MPa, and a reaction temperature of 230°C for 12 h. After the reaction, the reactor was cooled to room temperature, and then the gaseous products and liquid products were collected. The liquid products were centrifuged to obtain an oil phase, an aqueous phase, and a catalyst solid phase. The oil phase and the aqueous phase were then detected and analyzed by gas chromatography. The catalytic activity results of the products are shown in Table 1 below.
[0062] Example 7
[0063] The super-hydrophobic nickel-based NiSn@CA-PDVB catalyst prepared in Example 5 was applied to the reaction system of ethanol aqueous phase synthesis of higher alcohols. The reaction conditions were: 0.3 g of the catalyst prepared in Example 2, 0.88 g of sodium hydroxide, 5 g of ethanol, 5 g of water, an initial pressure of 0.1 MPa, and a reaction temperature of 230°C for 12 h. After the reaction, the reactor was cooled to room temperature, and then the gaseous products and liquid products were collected. The liquid products were centrifuged to obtain an oil phase, an aqueous phase, and a catalyst solid phase. The oil phase and the aqueous phase were then detected and analyzed by gas chromatography. The catalytic activity results of the products are shown in Table 1 below.
[0064] Example 8
[0065] This example provides a method for synthesizing superhydrophobic Ni@CS-PDVB.
[0066] The prepared nickel-based catalyst Ni@CS and the hydrophobic polymer PDVB prepared in Example 1 were ball-milled at a rotation speed of 300 rpm for 4 hours in a super-hydrophobic mass ratio of 1:1 to obtain a super-hydrophobic nickel-based Ni@CS-PDVB catalyst.
[0067] The Ni@CS is prepared by the following method:
[0068] S1. Dissolve 6.89 g nickel nitrate, 9.13 g citric acid carbon source and 0.096 g L-cysteine in deionized water and stir until completely dissolved; evaporate the mixture at 80° C. to gradually gel, and then dry at 100° C. until completely dry;
[0069] S2, placing the nickel-based catalyst gel precursor of S1 in an inert gas atmosphere at 550° C. for a controlled high-temperature self-reduction carbonization reaction for 2 hours to obtain a nickel-coated carbon-sulfur Ni@CS catalyst;
[0070] Example 9
[0071] The prepared nickel-based Ni@CS catalyst was applied to the reaction system of ethanol aqueous phase synthesis of higher alcohols. The reaction conditions were: 0.15g of the prepared nickel-based catalyst, 0.88g of sodium hydroxide, 5g of ethanol, 5g of water, an initial pressure of 0.1MPa, and a reaction time of 12h at 230°C. After the reaction, the reactor was cooled to room temperature, and then the gaseous products and liquid products were collected. The liquid products were centrifuged to obtain an oil phase, an aqueous phase, and a catalyst solid phase. The oil phase and the aqueous phase were then detected and analyzed by gas chromatography. The catalytic activity results of the products are shown in Table 1 below.
[0072] Example 10
[0073] The superhydrophobic nickel-based Ni@CS-PDVB catalyst prepared in Example 8 was applied to the reaction system of ethanol aqueous phase synthesis of higher alcohols. The reaction conditions were: 0.3 g of the catalyst prepared in Example 2, 0.88 g of sodium hydroxide, 5 g of ethanol, 5 g of water, an initial pressure of 0.1 MPa, and a reaction temperature of 230°C for 12 h. After the reaction, the reactor was cooled to room temperature, and then the gaseous products and liquid products were collected. The liquid products were centrifuged to obtain an oil phase, an aqueous phase, and a catalyst solid phase. The oil phase and the aqueous phase were then detected and analyzed by gas chromatography. The catalytic activity results of the products are shown in Table 1 below.
[0074] in:
[0075]
[0076]
[0077]
[0078] From the data in Table 1, it can be seen that when the nickel-based catalyst and the hydrophobic polymer PDVB are simply ball-milled, the ethanol conversion rate, the yield of alcohol products and the selectivity of high-carbon alcohol products are all improved to a certain extent compared with the catalyst before ball-milling. In addition, the ethanol conversion rate, the carbon yield of alcohol products and the selectivity of C6+ products of the catalyst without ball-milling of the hydrophobic polymer are all low.
[0079] Table 1 Catalytic performance test results of hydrophobic NiSn@C-SDB catalyst
[0080] catalyst Ethanol conversion Carbon yield of alcohol products C6+ product selectivity Ni@CA 67.6 36.1 50.50 Ni@CA-PDVB 76.1 45.4 58.06 NiSn@CA 74.6 48.5 59.17 NiSn@CA-PDVB 83.3 57.7 69.95 Ni@CS 93.8 67.0 73.59 Ni@CS-PDVB 98.8 79.5 80.11
[0081] In summary, it can be seen that the super-hydrophobic nickel-based catalyst synthesized by the inventive method is applied in the reaction of catalyzing ethanol one-step synthesis of higher alcohols, showing excellent catalytic efficiency, higher reaction activity and high selectivity to high-value C6+ higher-carbon alcohol products, and the selectivity of C6+ alcohol products can be improved to a certain extent. In addition, the raw materials of the present invention are simple to prepare and low in cost, and the reaction performance of the catalyst can be changed by simple ball milling, which is more conducive to its production application.
[0082] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A super hydrophobic catalyst for catalyzing ethanol-water phase coupling, characterized in that, The nickel-based catalyst and the super-hydrophobic polymer polydivinylbenzene are added into a ball mill according to a mass ratio of 1:0-4, and the ball milling is performed at a rotation speed of 200-600 rpm for 2-10 hours to obtain the product.
2. A super hydrophobic catalyst for catalyzing ethanol water phase coupling according to claim 1, characterized in that, The mass ratio of the nickel-based catalyst to the super-hydrophobic polymer polydivinylbenzene is 1:
1.
3. A super hydrophobic catalyst for catalyzing ethanol water phase coupling according to claim 1, characterized in that, The nickel-based catalyst is prepared by the following method: S1, dissolving the nickel salt and the carbon source precursor in a solvent, stirring at room temperature to form a complex to obtain a homogeneous solution, and then heating and stirring to form a nickel-based catalyst gel precursor; The molar ratio of the nickel salt to the carbon source is 1:2; S2. The nickel-based catalyst gel precursor of S1 is placed in an inert gas atmosphere and subjected to a controlled high-temperature self-reduction carbonization reaction at 550° C. for 2 hours to obtain a nickel-coated carbon Ni@CA catalyst.
4. A super hydrophobic catalyst for catalyzing ethanol water phase coupling according to claim 1, characterized in that, The nickel-based catalyst is prepared by the following method: S1, dissolving nickel salt, tin salt and carbon source precursor in a solvent, stirring at room temperature to form a complex to obtain a homogeneous solution, and then heating and stirring to form a nickel-tin bimetallic catalyst gel precursor; The molar ratio of Ni / Sn in the nickel salt and the tin salt is 20:1, and the molar ratio of Ni in the nickel salt to the carbon source precursor is 1:2; S2. The nickel-tin bimetallic catalyst gel precursor of S1 is placed in an inert gas atmosphere and subjected to a controlled high-temperature self-reduction carbonization reaction at 550° C. for 2 hours to obtain a nickel-tin carbon-coated NiSn@CA bimetallic catalyst.
5. A super hydrophobic catalyst for catalyzing ethanol water phase coupling according to claim 1, characterized in that, The nickel-based catalyst is prepared by the following method: S1. Dissolve nickel salt, carbon source precursor and L-cysteine in deionized water and stir until completely dissolved; evaporate the mixture at 80°C to gradually gel, and then dry at 100°C until completely dry; S2, placing the nickel-based catalyst gel precursor of S1 in an inert gas atmosphere at 550° C. for a controlled high-temperature self-reduction carbonization reaction for 2 hours to obtain a nickel-coated carbon-sulfur Ni@CS catalyst; The molar ratio of Ni in the nickel salt to the molar ratio of S in L-cysteine is 30:1; the molar ratio of Ni in the nickel salt to the carbon source precursor is 1:
2.
6. A super-hydrophobic catalyst for catalyzing ethanol water phase coupling according to any one of claims 2-4, characterized in that, The nickel salt includes nickel nitrate, nickel chloride, nickel acetate, and nickel hydroxide, preferably nickel nitrate; the tin salt includes tin nitrate, tin citrate, and tin chloride, preferably tin chloride; and the carbon source is citric acid.
7. A super hydrophobic catalyst for catalyzing ethanol water phase coupling according to claim 1, characterized in that, The polydivinylbenzene is prepared by the following method: 10 g of purified divinylbenzene is stirred in 50 g of solvent N,N-dimethylformamide at room temperature for 1 hour, then transferred to an autoclave, and heat-treated at 100°C for 12 hours. The obtained solid is washed with methanol and dried at 100°C overnight to obtain polydivinylbenzene.
8. the super hydrophobic catalyst described in claim 1 is used for catalyzing the coupling synthesis of higher alcohols in ethanol aqueous phase.
9. A method for synthesizing higher alcohols from ethanol in aqueous phase using a super-hydrophobic nickel-based catalyst, characterized in that: The super-hydrophobic catalyst according to claim 1 is used to form a reaction system with alkali, ethanol and water. Under a H2 atmosphere, the initial pressure is set to 0.1 MPa and the reaction is carried out at 230°C for 12 hours to synthesize high-carbon alcohols.
10. The method for synthesizing higher alcohols from ethanol in aqueous phase using a super-hydrophobic nickel-based catalyst according to claim 1, wherein: The mass ratio of superhydrophobic catalyst: alkali: ethanol: water is 0.3:0.88:5:5; the alkali can be sodium hydroxide or potassium hydroxide.
Citation Information
Patent Citations
NiSn / C core-shell composite nano-catalyst, preparation method and application thereof
CN112973707A
Solid alkali synergistic carbon-coated nickel-based amphiphilic phase transfer catalyst as well as preparation method and application thereof
CN114177908A
Preparation method of super-hydrophobic phosphoric acid-based geopolymer
CN114409286A
Recycling method of fuel cell stack
CN115084563A
Hydrophobic polymer coated modified sodium battery positive electrode material, preparation method and battery
CN115954447A
Cited By
Carbon-coated nickel-based super-hydrophobic catalyst as well as preparation method and application thereof
CN120618471A
Carbon-coated nickel-based super-hydrophobic catalyst, preparation method and application thereof
CN120618471B